中小學課程政策改革之研究：九年一貫課程的回顧與前瞻A Study on Curriculum Reform Policies of Elementary and Secondary School: Focusing on the Grade 1-9 - 吳俊憲（通訊作者）Chun-Hsien Wu (Journal of Curriculum Studies, 2010)
近年來，我國中小學課程面臨巨大變革，尤其是推動九年一貫課程改革可以說是一項新的里程碑，期望藉以培養具備人本情懷、統整能力、民主素養、鄉土與國際意識，以及能進行終身學習之健全國民。只是推動迄今，一些理想和現實產生落差，本文即著眼於此，針對九年一貫課程改革政策之形成背景及實施概況進行探究，然後探究重要改革議題（含能力指標與領域教學、學校本位課程與重大議題融入、中央－地方－學校課程權限劃分）之實施困境及爭議問題、推動成果及影響等。最後，歸納結果並提出改進建議，提供未來修訂課程政策方向之參考。The purposes of this study were to explore the curriculum reform policies of elementary and secondary school in Taiwan. Three issues of curriculum policies were analyzed and discussed: (1) the competence indicators and learning areas teaching; (2) the school-based curriculum development and integrating important social issues in instruction; (3) the distribution of jurisdiction and operating mechanisms relating to curricula at the central, local, and school levels. Finally, based on the results mentioned above, several suggestions for reforming curriculum policies of elementary and secondary school were proposed.